2024
DOI: 10.1021/acs.macromol.3c02243
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Crystallization Starting from Self-Nucleated Precursors

Ruijun Zhao,
Yingzhuo Liu,
Zhe Ma

Abstract: Flow-induced crystallization is a multistep process, in which precursors are often generated as a crucial ordering state intermediate between the initial amorphous state and the ultimate crystallite. In this work, the self-nucleation effect of isotactic polybutene-1 was employed to obtain the ordering precursors and to study flow-induced crystallization that started from both the self-nucleated precursors and the completely relaxed amorphous phase. This could answer the long-standing question whether the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…One of the fascinating aspects of studying polymer nucleation induced by flow is its multiscale and multistep processes, as demonstrated in Figure and supported by previous studies. ,,,,,,,, ,,,, The corresponding multiscale structural changes range from conformation of local segments to deformation of entire chains, and the multistage changes include conformation orders, orientation orders and crystal orders proposed by Li’s group. , In other words, the shish and kebab formation processes are continuous ones, which contain different steps: conformational transition/segmental orientation/chain extension, aggregation of oriented segments, formation of precursors, formation of oriented crystal nuclei or shish, and formation of kababs. ,,,,,,,, ,,,, First, under the action of flow, chain segments will gradually undergo orientation and conformational changes, while entire chains will be extended. , ,…”
Section: Flow-induced Polymer Crystal Nucleationmentioning
confidence: 65%
See 3 more Smart Citations
“…One of the fascinating aspects of studying polymer nucleation induced by flow is its multiscale and multistep processes, as demonstrated in Figure and supported by previous studies. ,,,,,,,, ,,,, The corresponding multiscale structural changes range from conformation of local segments to deformation of entire chains, and the multistage changes include conformation orders, orientation orders and crystal orders proposed by Li’s group. , In other words, the shish and kebab formation processes are continuous ones, which contain different steps: conformational transition/segmental orientation/chain extension, aggregation of oriented segments, formation of precursors, formation of oriented crystal nuclei or shish, and formation of kababs. ,,,,,,,, ,,,, First, under the action of flow, chain segments will gradually undergo orientation and conformational changes, while entire chains will be extended. , ,…”
Section: Flow-induced Polymer Crystal Nucleationmentioning
confidence: 65%
“…While experimental findings have demonstrated the emergence of precursors in flow field, their structural details remain a puzzle to researchers. ,,,,,,,, ,,,,,, Both Kanaya’s group ,, and Matsuba’s group , observed that precursors can contain a small number of crystallites in melts subjected to relatively high shear rates. Molecular simulations also offer insights into the microstructure details of the precursors.…”
Section: Flow-induced Polymer Crystal Nucleationmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, at relatively weak flow, recovery from the heterogeneous melt to the ideal homogeneous melt was enhanced through the accelerated re-entanglement process, and consequently, the flow-induced crystallization kinetics of the heterogeneous melt were unexpectedly reduced compared to those of the homogeneous melt. Our group exploited the enhanced phase transition from the tetragonal to trigonal phases of polybutene-1 to study the self-nucleated precursors and the coupled effect with flow . The results indicated that residual self-nucleated precursors starting from the heterogeneous melt act as crucial ordering structures to facilitate crystallization rather than destruction back to the completely relaxed melt, leading to much faster crystallization kinetics and higher orientation than those in the homogeneous melt with complete relaxation.…”
Section: Introductionmentioning
confidence: 99%